PEMANFAATAN GOOGLE EARTH SEBAGAI MEDIA PEMBELAJARAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI SISWA KELAS X SMA MUHAMMADIYAH 2 SURAKARTA - Siti Layinatul Halimah; Miftakhul Huda (LPPM Universitas PGRI Silampari Lubuklinggau, 2026)
The purpose of this study is to explain how to utilize Google Earth as a learning medium for descriptive essay writing skills for grade X students of SMA Muhammadiyah 2 Surakarta. This study uses a qualitative approach with a case study design. The data for this study are descriptive texts written by students in paragraph form using Google Earth. The data sources for this study were 28 grade X-3 students of SMA Muhammadiyah 2 Surakarta and one Indonesian teacher who teaches in the class. Data collection was carried out by observing student activities, interviewing Indonesian teachers, and documenting photos and videos of the learning process. Data analysis was carried out using the Spradley analysis model and content analysis techniques. Data validation used source triangulation techniques. Based on the data obtained, it can be seen that the use of Google Earth as a learning medium for essay writing has a positive influence in improving the quality of students' writing, which includes: (1) concrete and communicative writing, (2) structures that are in accordance with rules, and (3) increasing expressive power and accuracy in choosing diction. Based on the post-test results, there was a significant increase in 28 students, as many as 15 students (53.57%) obtained a score of 100, 11 students (39.29%) obtained a score of 90, and 2 students (7.14%) obtained a score of 80.